Vomiting and Abdominal Pain in a 5-Year-Old Male - Jonathan K. Williamson MD; Sarah Passarello MD; Ryan C. Kwong MD, MPH (SAGE Publishing, 2023)
This case describes small bowel obstruction secondary to a Meckel's Diverticulum in a 5-year-old male patient with a chief complain of abdominal pain and vomiting. We review the pathophysiology, diagnosis, and management of Meckel's Diverticulum. This case report highlights the importance of considering a broad differential diagnosis during a clinical workup.